The Valuation of Loss Firms: A Stock Market Perspective - Hannes Mohrschladt; Susanne Siedhoff (Abacus, 2024)
The proportion of exchange-listed firms with negative earnings has increased to over 40% in recent years. Previous research shows that the valuation of these loss firms is comparably difficult due to their uncertain future earnings path. Given these valuation issues, we argue that the stocks of loss firms should be particularly prone to mispricing such that simple firm value proxies might allow the prediction of subsequent stock returns. Supporting this hypothesis empirically, we find that book-to-market and revenue-to-price positively predict the cross-section of loss firms' stock returns. In particular, these value effects are significantly stronger compared to gain firms. Our further analyses support a behavioural mechanism for the empirical observations as the return predictability is disproportionately strong around earnings announcements and as analysts are too optimistic for loss firms with low values of book-to-market and revenue-to-price. Our analyses on short selling and option trading indicate that sophisticated investors are aware of the documented return predictability, but limits to arbitrage prevent an immediate correction of mispricing.
Keywords: 330; Firm valuation; Loss firms; Stock mispricing; Value effect